Winter prey eaudiobook - Sandford, John (Lucas Davenport, 1995)
Few writers have explored the human dark side with as much insight and power-and in Winter Prey, his shattering New York Times best-seller, Sandford tells his most ice-blooded tale of all. Minneapolis Lieutenant Lucas Davenport has tracked killers in cities across America. But even he may be unprepared to face the savage murderer hunting human prey in the Wisconsin woods this winter.